INDIKASI EARNINGS MANAGEMENT SEBELUM DEBT COVENANT SUDI EMPIRIS BADAN USAHA MILIK NEGARA - Andriyani, Lilik Andriyani (Universitas Muhammadiyah Magelang, 2004)
One of the reasons for earnings management is the motivation to abide by (debt covenant) the contract agreement. This earnings management is utilized by as effort to avoid the violation debt covenant. In positive accountancy theory about debt covenant hypothesis, earnings management done at the time of coming near debt covenant. Various study have studied this problem and use the bonus, dividend division etcetera as mechanism the debt covenant. This research differ from the previous study using obligation publication as agreement mechanism. This reaearch test the existence of indication of earnings management at debt covenant by using proxy discretionary accruals (abnormal accruals) by modified-Jones model to detect the existence of indication of Earnings management. Method used to analyse the data by using time series OLS regression for the data of research 10 or more and mean total accrual for the data of less than 10, and to tes the hypothesis raised to be used by t-test. This Research give the empirical evidence about existence of indication of earnings management boost up the earnings at period of before agreement and can prove the existence of bigger earnings management a company trussed by agreement from at unattached of agreement, this mateer is consistent with the previous research and can support the debt covenan hypothesis.